Optimierung der entspiegelten Schutzverglasung vor Glasmalereien am Kölner Dom. Issue 1 (25th March 2019) - Busse, Felix; Huber, Ulrich
Abstract : Optimization of anti‐reflective protective glazing in front of glass paintings at Cologne Cathedral . Cologne Cathedral has one of the largest collections of historic stained glass worldwide with windows spanning seven centuries. As you can appreciate on a daily basis, these windows have to withstand conditions that degrade and damage the glasses overtime. Historically the solution has been just to restore the stained glass. To make this a lasting solution, it has to be combined with the installation of protective glass that protects against weather conditions. The perception of protective glazing is essentially determined by the intensity and colour of the reflection of the light on the glass surface. In each case the individual viewing angle must be regarded. Through the use and optimization of an interference‐optical anti‐reflection system the visual perception of protective glazing on historic buildings can be positively influenced, making it virtually invisible to the eye.